2015
DOI: 10.1111/dme.12746
|View full text |Cite
|
Sign up to set email alerts
|

Condition‐related predictors of successful transition from paediatric to adult care among adolescents with Type 1 diabetes

Abstract: Several factors easily ascertained at a clinical encounter before transition can predict the likelihood of attendance in adult care, including age at diagnosis, mode of insulin administration, frequency of physician visits, and questions asked by patients during a transition visit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 28 publications
3
25
1
Order By: Relevance
“…Evidence points to a more successful transfer of care during the transition-age in patients using technology for insulin delivery and glucose monitoring (insulin pumps and CGM). [47][48][49] Larger randomized controlled trials are still needed to define patients that would most benefit from intervention, potential risks in relying on and promoting technology, and barriers to care needing to be addressed. 2.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence points to a more successful transfer of care during the transition-age in patients using technology for insulin delivery and glucose monitoring (insulin pumps and CGM). [47][48][49] Larger randomized controlled trials are still needed to define patients that would most benefit from intervention, potential risks in relying on and promoting technology, and barriers to care needing to be addressed. 2.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is growing evidence for the impact of structured and guided transition programs . Predictors for a successful transition were more intensified insulin treatment, better metabolic control, more visits in the pediatric department before transfer and more focus on the transition process . Especially, adolescents with poor metabolic control and a history of severe hypoglycemia have a higher mortality risk in early adulthood .…”
Section: Introductionmentioning
confidence: 99%
“…9 Although these studies found positive short-term health outcomes (better glycosylated haemoglobin (Hb1Ac) levels and less short-term complications) and follow-up rates, there is currently no evidence for (long-term) outcomes of TCs with regard to health outcomes, healthcare use, self-management and psychosocial functioning of young adults. Moreover, recent studies of TCs in other diagnostic groups did not include a controlled pre-post outcome evaluation, [19][20][21][22][23][24][25][26][27][28][29][30] and as such could not provide sound evidence on outcomes of TCs. In general, there is inconclusive evidence considering the effectiveness of transitional care.…”
Section: Introductionmentioning
confidence: 99%